Pengaruh Media Pembelajaran Geoboard Terhadap Hasil Belajar Matematika Kelas di SDN Baru 06 Jakarta - Fazriah, Sabila; Kasriman, Kasriman (Jurnal Ilmiah Global Education, 2025)
Based on data obtained through a pre-survey at SDN Baru 06 Jakarta, it is known that most students have difficulty in understanding mathematics material, especially geometry, which has an impact on low learning outcomes. This study aims to determine the effect of using geoboard learning media on the mathematics learning outcomes of grade V students. This research uses quantitative methods with a quasi-experiment design through a nonequivalent control group design approach. The sample consisted of two classes, namely the experimental class and the control class, each of which amounted to 30 students. The instrument used was an essay test of 10 questions, with pretest and posttest as a measuring tool for learning outcomes. Data analysis was carried out by testing normality, homogeneity, and hypothesis testing using Independent Sample T-Test. The results showed that there was a significant difference between the posttest results of the experimental class and the control class, where the average score of the experimental class students was higher (Mean = 79.67) than the control class (Mean = 63.07). The t-test shows a significance value of <0.001, which means that there is a positive effect of using geoboard media on student learning outcomes. In conclusion, learning math using geoboard media can improve the learning outcomes of grade V students, because it provides a more concrete and interesting learning experience.